A Lightweight Mutual Authentication Protocol for Secure IoT Communication in Resource-Constrained Environments - Dr. Michael Adeyemi (The American Journal of Engineering and Technology, 2026)
The rapid expansion of the Internet of Things (IoT) has enabled seamless connectivity among billions of resource-constrained devices, creating new opportunities in smart healthcare, industrial automation, smart cities, and cyber-physical systems. However, this connectivity introduces serious security challenges, particularly in the area of device authentication and secure communication. Mutual authentication is a fundamental requirement to ensure that both communicating entities verify each other before exchanging sensitive data. Traditional authentication mechanisms are often unsuitable for IoT environments due to their computational overhead, energy consumption, and communication latency. This paper proposes a lightweight mutual authentication protocol designed specifically for resource-constrained IoT environments. The proposed framework leverages efficient cryptographic primitives and physical unclonable functions (PUFs) to achieve secure, scalable, and low-overhead authentication. The protocol is evaluated conceptually against common IoT threats such as impersonation attacks, replay attacks, and man-in-the-middle attacks. Comparative analysis with existing state-of-the-art approaches demonstrates that the proposed solution significantly improves efficiency while maintaining strong security guarantees. The study also explores integration scenarios in Internet of Medical Things (IoMT) and edge-enabled IoT architectures.